Identification of an anatomical safe zone for humeral cerclage passage - Matthew T. Gulbrandsen, MD; Lea E. McDaniel, MD; Clayton H. Hui, BS; Jeremy R. Brown, MD; Taha M. Taka, MD; Marc G. Lubitz, MD; Anup A. Shah, MD; Evan S. Lederman, MD; Wesley P. Phipatanakul, MD (JSES International)
Background: Cerclage techniques have been used in the humerus in the setting of fractures and shoulder arthroplasty. Cerclage usage in the humerus has the potential to injure neurovascular structures. There is current literature describing deeper anatomic structures surrounding the humerus but not more superficial landmarks in reference to neurovascular structures. The purpose of this study was to determine safe zones for cerclage passage around the humerus. Methods: Eight fresh-frozen cadaveric specimens with no history of deformity, prior surgery, or trauma to the shoulder or arm were used in this study. A standard extended deltopectoral approach was performed in all 8 specimens. Dissection was performed to identify the various musculotendinous and neurovascular structures surrounding the humerus. Cerclage sutures were placed around the humerus. Measurements were made from the radial and axillary nerve to anatomic structures and the cerclage sutures. Results: The radial nerve entered the spiral groove on average 45.8 mm distal (range: 30.4 to 63.3 mm) to the inferior aspect of the pectoralis major tendon. Cerclage suture passed just distal to the inferior aspect of the pectoralis major tendon did not violate the radial nerve. The axillary nerve was located on the humerus an average of 5.3 mm (range: 2.4-10 mm) proximal to the superior aspect of the latissimus dorsi tendon insertion. A safe zone for cerclage passage was not identified distal to the radial nerve entering the spiral groove. Conclusion: The radial nerve entered the spiral groove on the humerus distal to the pectoralis insertion in all specimens. The axillary nerve started to contact the humerus proximal to the latissimus dorsi in all specimens. In this study, we found that cerclage passage medial to lateral from the latissimus dorsi proximally to the area just distal to the inferior pectoralis major insertion distally is a safe zone for cerclage passage.